Nonlinear effects in infrared action spectroscopy of silicon and vanadium oxide clusters: experiment and kinetic modeling1. Issue 39 (21st October 2015) - Calvo, Florent; Li, Yejun; Kiawi, Denis M.; Bakker, Joost M.; Parneix, Pascal; Janssens, Ewald
<x xml:space="preserve">Abstract</x> Nonlinear effects in infrared action spectroscopy are experimentally quantified and successfully modeled for different inorganic clusters.